MYOSIN HEAVY CHAIN ISOFORMS, FATTY ACID COMPOSITION, SENSORY EVALUATION AND QUALITY OF CINTA SENESE PIG MEAT - VELOTTO, S.; RABIE ASHKEZARY, M.; DE CAMILLIS, S.; TODARO, A. (Italian Journal of Food Science, 2018)
The aims of this study were to examine the effects of myosin heavy chain (MHC) isoforms on Cinta Senese meat and sensory quality. The research was carried out on 65 pigs and muscle samples characteristics such as MHC isoform, meat quality, fatty acid composition, and sensory were evaluated. The results demonstrated that MHC slow isoform content was significantly correlated with pH24h (r=0.25, P<0.05) and drip loss (r=-0.31, P<0.005), whereas the content of MHC isoforms was only weakly correlated with fatty acids. Sensory evaluation was done by a trained panel test and the results shown that the MHC fast/slow ratio was correlated with the juiciness (r=-0.32, P<0.005), off-flavor (r=0.33, P<0.01), and tenderness attributes (r=-0.42 to -0.46). We therefore conclude that the content of MHC isoforms can be one of the most important factors for examination of overall quality of Cinta Senese pigs.